The Ability of Prospective Science Teacher at UINSA to Design P5-PPRA Projects - Nur Wakhidah; Indayati, Tatik; Erman (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The Independent Curriculum emphasizes learning project For develop character in accordance values Pancasila students and students blessings lilalamin (P5-PPRA). Learning project requires a complicated process in accordance syntax learning projects and involve various parties. Research objectives This for analyze design learning project student prospective teachers. Research descriptive qualitative This conducted in the Science Education study program of UIN Sunan Ampel Surabaya. The number of students involved 29 people . Research started with collection document students, preparation of rubric indicators assessment, FGD and analysis document. Score data from rubric evaluation P5PPRA module analyzed using the binomial non-parametric test for know module indicator achievement P5PPRA project with SPSS application. Research results show H 1 accepted It means proportion students who have ability designing P5PPRA module with value 75 less from 85%. Mastered indicators student with Good is determine dimensions Pancasila students (76,7%). These results hinting before assistance teaching, students need deepen his knowledge and skills in compile facilitated P5PPRA module in lectures. The P5-PPRA project is important for prospective science teachers for implementation of meaningful learning.